1961
DOI: 10.1128/jb.81.1.44-50.1961
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Requirements for Bacterial Cell Wall Synthesis

Abstract: In the preceding paper (Shockman et al., 1961) the lytic properties of exponentially growing cells of Streptococcus faecalis have been described. Not only will washed and transferred exponential cells lyse but, under proper conditions, they eaD engage in either exponential growth or in postexponential cell wall synthesis. Some of the necessary conditions, and evidence for the synthesis of cell wall substances will be presented here. MATERIALS AND METHODS Methods of growth, washing, and transfer of S. faecalis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

1965
1965
1992
1992

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…Immunofluorescent reactive material was found VOL. 17,1977 sequestered throughout the macrophage cytoplasm, giving a brilliant granular fluorescent pattern ( Fig. 1).…”
Section: Distribution Of Radiolabel In Streptococcal Cell Walls the mentioning
confidence: 99%
See 2 more Smart Citations
“…Immunofluorescent reactive material was found VOL. 17,1977 sequestered throughout the macrophage cytoplasm, giving a brilliant granular fluorescent pattern ( Fig. 1).…”
Section: Distribution Of Radiolabel In Streptococcal Cell Walls the mentioning
confidence: 99%
“…Group A streptococcal cels (type 3, strain D58) were labeled with either [14C]alanine or [14C]glucose. Cells were cultured for 24 h in a modified medium consisting of 1 volume of "depleted broth" (filtered, spent medium of an 18-h Todd-Hewitt broth culture of group A streptococci) and 1 volume of "glucose-salts" medium modified from that of Shockman et al (17). To this medium was added 1 MCi of DL-[1-14C]alanine per ml (specific activity, 23.8 mCi/mmol; Amersham/Searle, Arlington Heights, Ill.).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent observations showed that exponentially growing and dividing cells of E. hirae were prone to autolysis which could be observed not only by the depletion of lysine but by placing bacteria from an exponentially growing culture into a culture medium lacking one or more nutritionally required precursors of peptidoglycan, including glutamic acid and glucose [10,16,17], or more simply, into a buffer of appropriate pH and concentration. These data led us to ask why growing and dividing bacteria should carry around with themselves such potentially suicidal enzyme activities.…”
Section: Autolysis Of E Hiraementioning
confidence: 99%
“…Cells were grown for 18 h with shaking at 37°C in brain heart infusion (Difco. Detroit, U.S.A. or Labm, Bury, U.K.), heat-inactivated horse serum (Gibco Europe, Paisley, U.K.), or a chemically defined medium (CDM) [6]. Cells were washed three times in saline and resuspended in water to an absorbance (470 rim) of 5.…”
Section: Introductionmentioning
confidence: 99%